17
Rewrite the expression simplified and using only positive exponents.
\(\displaystyle{ \displaystyle\left(\frac{1}{8}\right)^{-3}=
}\) \(\quad\)
18
Rewrite the expression simplified and using only positive exponents.
\(\displaystyle{ \displaystyle\left(\frac{1}{9}\right)^{-3}=
}\) \(\quad\)
19
Rewrite the expression simplified and using only positive exponents.
\(\displaystyle{\displaystyle {9x^{-12}}= }\)
20
Rewrite the expression simplified and using only positive exponents.
\(\displaystyle{\displaystyle {19x^{-3}}= }\)
21
Rewrite the expression simplified and using only positive exponents.
\(\displaystyle{\displaystyle {\frac{14}{x^{-4}}}= }\)
22
Rewrite the expression simplified and using only positive exponents.
\(\displaystyle{\displaystyle {\frac{8}{x^{-5}}}= }\)
23
Rewrite the expression simplified and using only positive exponents.
\(\displaystyle{\displaystyle {\frac{18x^{-9}}{x^{-26}}}= }\)
24
Rewrite the expression simplified and using only positive exponents.
\(\displaystyle{\displaystyle {\frac{8x^{-11}}{x^{-17}}}= }\)
25
Rewrite the expression simplified and using only positive exponents.
\(\displaystyle\frac{r^{-3}}{\left(r^{4}\right)^{10}}=\)
26
Rewrite the expression simplified and using only positive exponents.
\(\displaystyle\frac{r^{-2}}{\left(r^{11}\right)^{7}}=\)
27
Rewrite the expression simplified and using only positive exponents.
\(t^{-11}\cdot t^{6}=\)
28
Rewrite the expression simplified and using only positive exponents.
\(t^{-5}\cdot t^{4}=\)
29
Rewrite the expression simplified and using only positive exponents.
\((9x^{-17})\cdot (6x^{6})=\)
30
Rewrite the expression simplified and using only positive exponents.
\((6x^{-10})\cdot (10x^{7})=\)
31
Rewrite the expression simplified and using only positive exponents.
\(\left(-5y^{-4}\right)^{-2}\)
32
Rewrite the expression simplified and using only positive exponents.
\(\left(-2y^{-16}\right)^{-3}\)
33
Rewrite the expression simplified and using only positive exponents.
\(\left(3y^{8}\right)^{4}\cdot y^{-22}=\)
34
Rewrite the expression simplified and using only positive exponents.
\(\left(3r^{3}\right)^{3}\cdot r^{-4}=\)
35
Rewrite the expression simplified and using only positive exponents.
\(\left(r^{4}t^{8}\right)^{-3}=\)
36
Rewrite the expression simplified and using only positive exponents.
\(\left(t^{6}y^{14}\right)^{-3}=\)
37
Rewrite the expression simplified and using only positive exponents.
\(\left(t^{-11}x^{10}\right)^{-3}=\)
38
Rewrite the expression simplified and using only positive exponents.
\(\left(x^{-4}r^{6}\right)^{-3}=\)
39
Rewrite the expression simplified and using only positive exponents.
\(\displaystyle\left(\frac{x^{6}}{2}\right)^{-3}=\)
40
Rewrite the expression simplified and using only positive exponents.
\(\displaystyle\left(\frac{y^{15}}{4}\right)^{-4}=\)